Pemetaan Riset Reformasi Birokrasi di Indonesia: Research Mapping of Bureaucratic Reform in Indonesia - Fikri Habibi (Pusjar SKPP Lembaga Administrasi Negara, 2020)
The purpose is to map the research on the bureaucratic topics in Indonesia and get a development description of its changes from the bureaucratics reform and achievements of its changes in Indonesia. The study obtained from 105 articles published on journal accredited Sinta 1 and 2 from 2010 to 2020. Based on the amount, it showed that from 2010 to 2014 was relatively stable, from 2015 to 2019 were fluctuated with an increase in 2016 followed by continued decline. Research on bureaucratic reform has covered the institutions/organizations, governance, apparatus and public services including achievement of eight change areas. . However, there is still less research that discusses about political-bureaucratic relations, cultural and efforts to change mind set and culture set of apparatus. There are 17 researches about central government bureaucracy, 44 researches relate to regional bureaucracy, 43 researches of government organizations, and 1 research about village bureaucracy. This study showed that the agenda of bureaucratic reform has not yet reached the expected significant effectiveness. Future bureaucratic reform can discuss the topics that lack or earn non-optimal results and received less attention from previous research. In short, it needs synchronization between the research of bureaucratic reform with the Grand Design of Bureaucratic Reform 2010 to 2025 Keywords: Research Mapping, Bureaucratic Reform, Indonesia Abstrak Tujuan dari studi ini melakukan pemetaan terhadap riset reformasi birokrasi di Indonesia untuk mendapatkan gambaran perkembangannya, baik dari aspek-aspek reformasi birokrasi maupun capaian perubahannya. Studi dilakukan pada artikel-artikel yang dipublikasi pada jurnal yang terdata pada Sinta 1 dan 2 dari tahun 2010-2020 dan diperoleh 105 artikel. Dari jumlah penelitian, periode 2010-2014 relatif stabil, sementara tahun 2015-2019 terjadi fluktuasi dengan peningkatan jumlah riset tahun 2016 dan selanjutnya terjadi penurunan. Topik riset reformasi birokrasi sudah mencakup semua aspek, yaitu kelembagaan/organisasi, tata laksana, aparatur dan pelayanan publik termasuk capaian delapan area perubahan. Akan tetapi, sedikit sekali riset yang membahas tentang hubungan politik–birokrasi, aspek budaya dan upaya mengubah mind set dan culture set aparatur. Terdapat 17 riset tentang birokrasi pemerintah Pusat, 44 riset birokrasi daerah, 43 riset organisasi pemerintahan secara umum, dan 1 riset birokrasi desa. Studi ini menunjukan bahwa agenda reformasi birokrasi belum mencapai efektivitas yang signifikan. Riset reformasi birokrasi ke depan dapat diarahkan pada topik-topik yang kurang atau belum menunjukkan hasil yang optimal dan yang sedikit mendapatkan perhatian pada riset sebelumnya. Perlu ada sinkronisasi antara riset reformasi birokrasi dengan Grand Design Reformasi Birokrasi 2010-2025. Kata Kunci: Pemetaan Riset, Reformasi Birokrasi, Indonesia